The relationship between social Networking and Student-athlete Well-Being - Portela, L. K. (Auburn University, 2019)
Young adults ages 18-29 were found to be the most avid users of social networks (Pew Research Center, 2018). Engagement with social networks has been found to have both positive and negative impacts on well-being. Research has explored the relationship between social network use and college students, however there has been little focus on how the subpopulation ofstudent-athletes are impacted. The purpose of this study was to develop an understanding of the relationships among student-athlete social networking use, athletic identity, and well-being through the lens of emerging adulthood. Participants of this studywere a national sample of 95 Division I student-athletes. The research study established that student-athletes endorse the five dimensions of emerging adulthood and have a strong athletic identity. In addition, this study found that the less student-athlete`s used social networking the higher they scored on autonomy/ PWB. There were no differences in social networking use based on age, gender, or academic year however, scores on the autonomy subscale of PWB decreased as student-athletes got older. Further,female student-athletes scored higher on the autonomy and positive relations with others subscales of PWB. Lastly, the results showed that having more satisfying relationships with others and having goals in life results in higher levels of athletic identity forstudent-athletes.These findings can be used by counselors, athletic department personnel, and other professionals working with student-athletes to improve well-being and improve the overall student-athlete experience.